A Pharmacokinetic Study of Amphotericin B Lipid Complex Injection (Abelcet) in Patients with Definite or Probable Systemic Fungal Infections - Adedoyin, Adedayo (American Society for Microbiology, 2000)
This study describes a pharmacokinetic evaluation of amphotericin B (AMB) lipid complex injection (ABLC or Abelcet) in 17 patients with systemic fungal infection administered 5 mg/kg of body weight/day by infusion for 10 to 17 days. The results showed that AMB exhibited multiexponential disposition with high clearance, large volume of distribution at steady state, and long apparent elimination half-life but no evidence of accumulation in the blood after multiple daily doses. The results confirm previous observations and further reinforce the suggestion that ABLC may exist as a depot in the tissues from which free AMB is slowly released to limit exposure.